A Quantitative Study on the Factors Impacting Entrepreneurial Intention Of Social Sciences Students in Chengdu, China - Luo, Shiwei (Scholar: Human Sciences, 2024)
Purpose: Research on college students’ entrepreneurial attitudes and intentions has received increasing attention in recent years. This paper aims to explore the factors influencing entrepreneurial attitudes and intentions of college students majoring in Social Science at public universities in Chengdu, China. A conceptual framework was established with seven potential variables, subjective norm, entrepreneurial attitude, desirability, educational support, self-efficacy, perceived behavioral control, and entrepreneurial intention. Research design, data, and methodology: The researcher distributed questionnaires to 500 undergraduates majoring in Social Science at the targeted public university. This sampling strategy is to collect data from the survey using judgmental, quota and convenience sampling. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were used to analyze the data. In addition, model goodness-of-fit, correlation validity, and reliability tests for each factor were utilized. Results: The result demonstrated a significant effect between each potential variable, thus proving all hypotheses valid. Conclusions: Ultimately, this quantitative study concludes that public university administrators and teaching staff should strengthen the process of shaping and nurturing entrepreneurial attitudes among college students, enhancing the entrepreneurial appeal and emphasizing entrepreneurship education to improve entrepreneurial success based on the significant influence relationships between the potential variables verified in this study.